Profil Vertikal dan Luas Bidang Dinamika Harian Gradien Suhu Air Danau Tondano di Lokasi Budidaya dan Luar Lokasi Budidaya Ikan - Elroy Eden Egeten; Tineke Makahinda; Farly Tumimomor (Jurnal FisTa : Fisika dan Terapannya, 2023)
This study aims to determine the temporal and spatial function of water temperature and the function of the dynamics of Lake Tondano water temperature gradient. This research method was carried out on two transects, namely at the cultivation site and outside the fish farming site. By taking data at nine different depth positions for 24 hours. Measurement time starts at 05:00 am to 05:00 am, with a time interval of 2 hours. Measurement positions according to vertical distance from the top of the water surface are 0 cm, 10 cm, 30 cm, 60 cm, 100 cm, 150 cm, 220 cm, 300 cm and 400 cm. Data processing is done by arranging the data format in matrix form, then analyzed using a program or software that includes temporal and spatial functions, functions and area of the gradient dynamics field. The results of this study show mathematical modeling that produces a continuous function of temporal and spatial changes in microclimate variables that allow the development of new parameters, namely water temperature gradient dynamics. The study was conducted on two different transects with lake ecosystem and environmental conditions that showed that the area of the field formed by the daily dynamics curve of the water temperature gradient was different for both transects.